Deglaciation and Holocene climate change in the western Peruvian Andes - Weng, C. Y.; Bush, M. B.; Curtis, J. H.; Kolata, A. L.; Dillehay, T. D.; Binford, M. W. (Quaternary Research, 2006)
Pollen, charcoal, magnetic susceptibility, and bulk density data provide the first paleoecological record spanning the last 33,000 years from the western cordillera of the Peruvian Andes. Sparse super-puna vegetation existed before 30,000 cat yr B.P. around Lake Compuerta (3950 m elevation), prior to a sedimentary hiatus that lasted until c. 16,200 cat yr B.P. When sedimentation resumed, a glacial foreland or super-puna flora is represented in which Polylepis was a significant element. Glacial outwash, marked by high sedimentary magnetic susceptibility, increased from c. 16,200 cat yr B.P. and reached a peak at c. 13,200 cat yr B.P. Between c. 12,500 cat yr B.P. and 10,000 cat yr B.P., magnetic susceptibility was reduced. Vegetation shifts suggest a cool dry time, consistent with regional descriptions of the Younger Dryas event. Deglaciation resumes by 10,000 cat yr B.P. and the last ice is lost from the catchnient at similar to 7500 cat yr B.P. During the early Holocene warm and dry period between 10,000 and 5500 cat yr B.P., Alnus expanded in downslope forests. Alnus declined in abundance at 5500 cat yr B.P. when wetter and cooler conditions returned and human activity intensified. Maize (Zea mays) pollen first occurred in the core at similar to 2600 cat yr B.P., indicating a minimum age for local agriculture. An increase in Alnus pollen abundance at similar to 1000 cat yr B.P. could be due to human activity or perhaps due to a regional climate change associated with cultural turnover elsewhere in the Andes at this time. (c) 2006 University of Washington. All rights reserved.
058upTimes Cited:27Cited References Count:55

Abrupt climate change and pre-Columbian cultural collapse - Brenner, M.; Hodell, D. A.; Curtis, J. H.; Rosenmeier, M.; Binford, M. W.; Abbott, M. B. (Interhemispheric Climate Linkages, 2001)
id: 1408

A 3,500 14C yr. high-resolution record of lake level changes in Lake Titicaca, South America - Abbott, M. B.; Binford, M. W.; Brenner, M.; Kelts, K. R. (Quaternary Research, 1997)
Sediment cores collected from the southern basin of Lake Titicaca (Bolivia/Peru) on a transect from 4.6 m above overflow level to 15.1 m below overflow level are used to identify a new century-scale chronology of Holocene lake-level variations. The results indicate that lithologic and geochemical analyses on a transect of cores can be used to identify and date century-scale lake-level changes. Detailed sedimentary analyses of subfacies and radiocarbon dating were conducted on four representative cores. A chronology based on 60 accelerator mass spectrometer radiocarbon measurements constrains the timing of water-level fluctuations. Two methods were used to estimate the14C reservoir age. Both indicate that it has remained nearly constant at ∼25014C yr during the late Holocene. Core studies based on lithology and geochemistry establish the timing and magnitude of five periods of low lake level, implying negative moisture balance for the northern Andean altiplano over the last 3500 cal yr. Between 3500 and 3350 cal yr B.P., a transition from massive, inorganic-clay facies to laminated organic-matter-rich silts in each of the four cores signals a water-level rise after a prolonged mid-Holocene dry phase. Evidence of other significant low lake levels occurs 2900–2800, 2400–2200, 2000–1700, and 900–500 cal yr B.P. Several of the low lake levels coincided with cultural changes in the region, including the collapse of the Tiwanaku civilization.
id: 173; jpc

Climate variation and the rise and fall of an Andean civilization - Binford, M. W.; Kolata, A. L.; Brenner, M.; Janusek, J. W.; Seddon, M. T.; Abbott, M.; Curtis, J. H. (Quaternary Research, 1997)
Paleolimnological and archaeological records that span 3500 years from Lake Titicaca and the surrounding Bolivian-Peruvian altiplano demonstrate that the emergence of agriculture (ca. 1500 B.C.) and the collapse of the Tiwanaku civilization (ca. A.D. 1100) coincided with periods of abrupt, profound climate change, The timing and magnitude of climate changes are inferred from stratigraphic evidence of lake-level variation recorded in C-14-dated lake-sediment cores. Paleolake levels provide estimates of drainage basin water balance. Archaeological evidence establishes spatial and temporal patterns of agricultural field use and abandonment. Prior to 1500 B.C., aridity in the altiplano precluded intensive agriculture. During a wetter period from 1500 B.C. to A.D. 1100, the Tiwanaku civilization and its immediate predecessors developed specialized agricultural methods that stimulated population growth and sustained large human settlements, A prolonged drier period (ca. A.D. 1100-1400) caused declining agricultural production, field abandonment, and cultural collapse. (C) 1997 University of Washington.
Wu887Times Cited:148Cited References Count:53